Patient Satisfaction with Pharmaceutical Services at the Outpatient Pharmacy Installation of Hospital X, Bandar Lampung City - Yasmin Al Illyyin; Oktafany, Oktafany; Dwi Aulia Ramdini; Ihsanti Dwi Rahayu (Jurnal EduHealth, 2025)
As the main referral hospital in Lampung Province, evaluating the quality of pharmaceutical services at Hospital X is necessary. Periodic assessment of patient satisfaction is essential to maintain service quality in accordance with expectations. Therefore, this study aims to evaluate the level of patient satisfaction with pharmaceutical services at the Outpatient Pharmacy Installation of Hospital X in Bandar Lampung City. This study employed a cross-sectional survey design, with a purposive sampling technique applied to outpatients or their companions during April–May 2025. Data were collected using the SERVQUAL questionnaire, which consists of five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. The instrument was tested for validity (r count > r table) and reliability (Cronbach's alpha ≥ 0.6), and was declared valid and reliable. The data were analyzed by calculating the gap between patients' expectations and perceptions for each service dimension. A total of 354 respondents expressed being very satisfied with the tangibility (85.3%), reliability (87.7%), assurance (84.1%), and empathy (82.5%) dimensions, and satisfied with the responsiveness dimension (75.8%). All dimensions showed negative gaps (−0.534), with the largest gap in responsiveness (−0.84), indicating a significant discrepancy between patient expectations and experiences. The smallest gap was in reliability (−0.36), indicating that this dimension was closest to meeting patient expectations. Overall, outpatient satisfaction with pharmaceutical services at the Pharmacy Installation of Hospital The responsiveness dimension has the highest gap and should be the primary focus for improvement in order to enhance service quality.